Antiviral Prescriptions to U.S. Ambulatory Care Visits with a Diagnosis of Influenza before and after High Level of Adamantane Resistance 2005–06 Season - Hsieh, Yu-Hsiang (Public Library of Science, 2010)
BACKGROUND: Rapid emergence of influenza A viruses resistance to anti-influenza drugs has been observed in the past five years. Our objective was to compare antiviral prescription patterns of ambulatory care providers to patients with a diagnosis of influenza before and after the 2005–2006 influenza season, which was temporally concordant with the emergence of adamantane resistance. We also determined providers' adherence to Centers for Disease Control and Prevention (CDC) 2006 interim treatment guidelines for influenza after the dissemination of guidelines. METHODOLOGY/PRINCIPAL FINDINGS: We conducted a multi-year cross-sectional analysis using 2002–2006 data from the national representative ambulatory care surveys, National Ambulatory Medical Care Survey and National Hospital Ambulatory Medical Care Survey. Our main outcome measure was prescription of any anti-influenza pharmaceutical medication, including amantadine, rimantadine, oseltamivir, and zanamivir. Analyses were performed using procedures taking into account the multi-stage survey design and weighted sampling probabilities of the data source. Overall, there were 941 visits to U.S. ambulatory care providers for which the diagnosis of influenza was made, representing 12,140,727 visits nationally. Antiviral drugs were prescribed in 21.7% of visits. Even though prescription rates were not significantly different by influenza season (2001–02: 26.4%; 2002–03: 11.2%; 2003–04: 16.5%; 2004–05: 18.0%; 2005–06: 35.8%; 2006–07: 46.5%, p = 0.061), significantly higher prescription rates were observed in the high adamantane resistance period (18.7% versus 37.0%, p = 0.023), and after the announcement of the 2006 guidelines (18.5% versus 38.8%, p = 0.032). Use of adamantanes decreased over time, in that they were commonly used during influenza seasons 2001–03 (60.1%), but used much less frequently during seasons 2003–05 (31.9%), and used rarely after high adamantane resistance emerged (2.2%) (p<0.001). Adherence to 2006 guidelines was 97.7%. After March 2006, no prescriptions for adamantanes were given to patients with a diagnosis of influenza. CONCLUSIONS/SIGNIFICANCE: In this nationally representative study of U.S. ambulatory care visits, we found a complete absence of the use of adamantanes in all ambulatory care settings after March 2006, closely corresponding to release of the 2006 CDC interim guidelines. Adherence to such practice is an essential element for control and prevention of influenza, especially during the era of emergence of resistance to anti-viral drugs.